2010
DOI: 10.1080/14733140903370228
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia and the school counsellor: A Maltese case study

Abstract: Aim: This paper seeks to understand whether Maltese school counsellors are equipped to deal with dyslexic clients, considers whether specific strategies need to be used, and what positive effects, if any, counselling has on these clients. Previous studies: A literature review on self‐concept and techniques on how to improve the self‐concept of children with Learning Disabilities (LD)/Specific Learning Difficulties (SpLD) will place the current study in context. Method: Questionnaires (available from the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
2
13
0
1
Order By: Relevance
“…Similarly, Olkin (2002) noted that most professional counselors often engage in cross-cultural counseling with IWDs without sufficient training, which significantly increases the risk of client attrition, resistance to counseling intervention, and unsuccessful counseling outcomes in this population. Other studies (Bell, 2013;Falzon & Camilleri, 2010;Milsom & Akos, 2003;Walker, 2009) with counselors in various counseling settings (e.g., college counseling, mental health counseling, school counseling) also reported that counselors received very little training about disability issues. These findings imply that although IWDs continue to grow and their mental health needs are diverse, very few counseling programs provide requisite disability-competence training to build awareness, knowledge, and skills for their students who will serve clients with disabilities (Artman & Daniels, 2010;Olkin & Taliaferro, 2006;Pledger, 2003).…”
Section: Discussion Of Disability In Counselor Educationmentioning
confidence: 99%
“…Similarly, Olkin (2002) noted that most professional counselors often engage in cross-cultural counseling with IWDs without sufficient training, which significantly increases the risk of client attrition, resistance to counseling intervention, and unsuccessful counseling outcomes in this population. Other studies (Bell, 2013;Falzon & Camilleri, 2010;Milsom & Akos, 2003;Walker, 2009) with counselors in various counseling settings (e.g., college counseling, mental health counseling, school counseling) also reported that counselors received very little training about disability issues. These findings imply that although IWDs continue to grow and their mental health needs are diverse, very few counseling programs provide requisite disability-competence training to build awareness, knowledge, and skills for their students who will serve clients with disabilities (Artman & Daniels, 2010;Olkin & Taliaferro, 2006;Pledger, 2003).…”
Section: Discussion Of Disability In Counselor Educationmentioning
confidence: 99%
“…Learned helplessness is commonly exhibited by undergraduates with LD (Falzon & Camilleri, 2010;Klassen, Krawchuk, Lynch & Rajani, 2008;Voughn & Fuchs, 2003;Peleg, 2011). As such, the current intervention aimed to design a program that successfully delivered an encouraging and rewarding learning environment for students with LD while also providing training exercises that effectively trained their working memory.…”
Section: Discussionmentioning
confidence: 99%
“…I remember one fourth‐former with a profile of dyslexia. She had been so discouraged that she had even given up training with a national sports' team (Falzon & Camilleri, ; Riley & Rustique‐Forrester, ). She was feeling lonely, had been bullied and was even feeling suicidal.…”
Section: Methods and Aim Of Studymentioning
confidence: 99%
“…Her mother was at her wits' end. I encouraged her to resume her training, helped her boost her self‐esteem and to be assertive when necessary (Falzon & Camilleri, ). This led to her academic achievement being significantly improved (Alexander‐Passe, ; Kannangara, ).…”
Section: Methods and Aim Of Studymentioning
confidence: 99%